Pengaruh Penggunaan Filter Non Original Terhadap Kerusakan Bucket Control Valve Excavator 320D - Darma Aviva; Abdul Halim; Baso Cante; Abdul Muis (Politeknik Negeri Samarinda, 2021)
The hydraulic oil filter is one of the components contained in the hydraulic system which functions to filter the impurities contained in the oil so that it does not circulate into the system. The purpose of this study was to determine the performance of the original and non-original filters in relation to the damage that occurred to the control valve. The results indicated that the damage to the spool valve was caused by hydraulic oil contaminated with water, resulting in corrosion on its surface. Visual inspection of the hydraulic oil filter reveals particles found in the filer element.